BS23 Gender and aspirin impact generation of procoagulant oxidized phospholipids by platelets in a healthy human cohort. (May 2019) - Protty, Majd; Brasher, Christopher; Tyrrell, Victoria; Rodrigues, Patricia; Aldrovandi, Maceler; Obaji, Samya; Jenkins, P Vince; Collins, Peter; O'Donnell, Valerie
Abstract : Background: Phospholipids on the surface of platelets play a key role in supporting coagulation in both health and disease. Alterations to phospholipid composition in platelets can contribute to thrombotic and bleeding disorders. We recently identified pro-coagulant enzymatically oxidized phospholipids (eoxPL) generated by platelets in response to thrombin activation via cyclooxygenase-1 (COX) and 12-lipoxygenase (LOX). It is not known how these lipids vary in relation to aspirin (a COX inhibitor) supplementation and/or gender. Methods: Twenty-eight healthy volunteers (14 males, 14 females) donated blood for platelet isolation at baseline (following a 14-day NSAID washout) and after 7-day supplementation with 75 mg aspirin. Repeat sampling took place 2 months and 4 months later to account for variations over time. Lipids were extracted from platelets either basally or following 30 min thrombin activation then analysed using liquid chromatography with tandem mass-spectrometry (LC-MS/MS) for the 49 most abundant eoxPL molecular species. Results: The majority (96%) of eoxPL increased in response to thrombin activation of platelets. Gender differences were observed with a trend towards higher levels generated by females. Correlation analysis highlighted clustering of eoxPL by enzymatic origin (12-LOX versus COX-1). Aspirin supplementation decreased eoxPL generated via COX-1 in both genders, but in males it increased levels of those generated by 12-LOX (p<0.05). Importantly, elevated levels of 12-hydroxyeicosatetraenoic acid (12-HETE)-containing eoxPL, which are known to be procoagulant, were observed. In contrast, generation of free 12-HETE was not affected by aspirin. Conclusion: In this study, we found an influence of both gender and aspirin supplementation on the generation of eoxPL in thrombin-activated platelets from healthy volunteers. Further characterisation of the gender influence may reveal novel mechanisms that contribute to the risk of arterial thrombosis in human populations. Conflict of interest: None declared